2016
DOI: 10.1002/eqe.2791
|View full text |Cite
|
Sign up to set email alerts
|

Seismic analysis of a curved bridge considering deck‐abutment pounding interaction: an analytical investigation on the post‐impact response

Abstract: Summary Horizontal curved bridges are very common at intersections and at the changing angle of bridge alignment. Almost in every previous earthquake report, it can be seen that the columns of a curved segment experience torsional damage, and the curved decks are unseated from the abutment support. The main reason behind that phenomenon is the in‐plane deck rotation which results because of the complex dynamic coupling between two longitudinal directional vibrations. The curved decks are susceptible to deck ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This model has been developed based on the following fundamental assumptions: The deck is rigid and continuous in its own plane. This assumption is valid for the analytical modeling of short-span highway bridges, and has been used widely to estimate the seismic response of straight (Meng and Lui, 2000; Meng et al., 2001;), skew (Maleki, 2001; Kalantari and Amjadian, 2010), and horizontally curved highway bridges (Amjadian and Agrawal, 2016, 2017; Banerjee et al., 2017). The columns and bearings supporting the deck at abutments remain elastic during the motion of the deck.…”
Section: Mathematical Modeling Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…This model has been developed based on the following fundamental assumptions: The deck is rigid and continuous in its own plane. This assumption is valid for the analytical modeling of short-span highway bridges, and has been used widely to estimate the seismic response of straight (Meng and Lui, 2000; Meng et al., 2001;), skew (Maleki, 2001; Kalantari and Amjadian, 2010), and horizontally curved highway bridges (Amjadian and Agrawal, 2016, 2017; Banerjee et al., 2017). The columns and bearings supporting the deck at abutments remain elastic during the motion of the deck.…”
Section: Mathematical Modeling Of the Problemmentioning
confidence: 99%
“…It was also concluded that the natural frequency of this mode is strongly affected by the presence of an external cross bracing system between the steel boxes (Androus et al., 2017). In addition to the studies conducted on the calculation of the natural frequencies and mode shapes of horizontally curved bridges, there are many other studies that have focused on the different features of the dynamic behavior of horizontally curved bridges such as the sensitivity of their dynamic response to seismic pounding (Amjadian and Agrawal, 2016, 2017, Banerjee et al., 2016, 2017), nonlinear seismic response (Seo and Linzell, 2013; Amirihormozaki et al., 2015), seismic protection (Kataria and Jangid, 2016), and interaction with high-speed trains under frequent earthquakes (Zeng and Dimitrakopoulos, 2016), which all show the importance of understanding the complicated dynamic behavior of such bridges.…”
Section: Introductionmentioning
confidence: 99%
“…Dimitrakopoulos [ 15 ] revisited the seismic response of short skew bridges and proposed a novel nonsmooth rigid body approach to study the seismic pounding response involving oblique friction multicontact phenomena. Banerjee et al [ 16 ] used nonsmooth techniques to consider deck-abutment pounding interactions of curved bridges under deck rotation. These studies reveal the law of bridge pounding response from different angles; however, they all simplify the bridge to a spring-mass model or a beam bar model.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Karnopp friction model, Amjadian and Agrawal [11] investigated the influence of pounding on rigid-body motion of horizontally curved bridges during strong earthquakes. Banerjee et al [12] studied the dynamic response sensitivity of horizontally curved bridges under seismic impact and assessed the influence of columns, bent arrangement, and gap distances on the structural response. Julian et al [13] studied the rotations and displacements of curved bridge superstructures caused by flexural-torsional interaction under seismic loading.…”
Section: Introductionmentioning
confidence: 99%
“…is complex phenomenon is analytically studied for a single-impact case during deck-to-deck pounding between two curved bridge segments. Based on a previous investigation [12] on the impact between the abutment and the deck of a curved bridge, this paper studies the problem of impact between bridge segments of a curved bridge. e main contributions are as follows: first, the mechanism of deck rotation caused by the impact between bridge segments of a curved bridge is explained.…”
Section: Introductionmentioning
confidence: 99%